PENGARUH WORKING CAPITAL TURNOVER, CASH RASIO, DAN INVENTORY TURNOVER TERHADAP PROFITABILITAS DENGAN MENGGUNAKAN RASIO (ROI) PADA PERUSAHAAN SEKTOR CONSUMER GOODS INDUSTRY DI BURSA EFEK INDONESIA PERIODE2016-2018 - Mayani Manullang; Maya Agustina Tanjung; Sarbenny Ferdinata Sinuhaji; Friska Defrinayati (JURNAL GLOBAL MANAJEMEN, 2019)
This research aims at testing and analyzing the effect of Working Capital Turnover, Cash RatioandInventory Turnover on profitability (ROI) on Consumer Goods Industry companies registered in Indonesia Stock Exchange for 2016 – 2018 period. Research method used in this research is quantitative meanwhile the kind of this research is descriptive quantitative and its nature is explanatory. The population of this research is 38 consumer goods industry companies that meet the criteria. The samples are as many as 17 companies that have been taken by using purpose sampling technique. Data analysis was done by using multiple linear regression analysis with classical assumption test. Simultaneously, research finding shows that Working Capital Turnover, Cash Ratio, and Inventory Turnover affect significantly on profitability (ROI) of companies in Consumer Goods Industry sector registered in Indonesia Stock Exchange for 2016 – 2018 period in which the result is 6,792 ≥ 2,82 and 0.001 ≤ 0,05. Partially, Working Capital Turnover does not affect and insignificant on profitability (ROI) meanwhile Cash Ratio affects positively and significantly on profitability (ROI).Inventory Turnoveraffects negatively and insignificant on profitability (ROI). From the results of the determination analysis coefficient, it was taken that the value of AdjustedR2 shows the variety of profitability (ROI) variable that can be explained by variable variation Working Capital Turnover, Cash Ratio, and Inventory Turnover as many as 27% meanwhile the rest is as many as 73% that can be explained by other variable variations.